Adaptive Disorder Control in Data Stream Processing - Kim, Hyeon Gyu; Kim, Cheolgi; Kim, Myuong Ho (Computing and Informatics, 2012)
Out-of-order tuples in continuous data streams may cause inaccurate query results since conventional window operators generally discard those tuples. Existing approaches use a buffer to fix disorder in stream tuples and estimate its size based on the maximum network delay seen in the streams. However, they do not provide a method to control the amount of tuples that are not saved and discarded from the buffer, although users may want to keep it within a predefined error bound according to application requirements. In this paper, we propose a method to estimate the buffer size while keeping the percentage of tuple drops within a user-specified bound. The proposed method utilizes tuples' interarrival times and their network delays for estimation, whose parameters reflect real-time stream characteristics properly. Based on two parameters, our method controls the amount of tuple drops adaptively in accordance with fluctuated stream characteristics and keeps their percentage within a given bound, which we observed through our experiments.